Environmental Management and Governance: Advances in Coastal and Marine Resources - Finkl, Charles W (Springer, 2015)
This book deals with recent advances in coastal marine environmental management and governance. Various chapters consider new aspects of conservation, assessment of ecosystem health status, environmental survey and protection, frameworks of ocean service and governance, new applications of geo processing and GIS technology, beach management, aquaculture site selection, assessment of water quality (brine disposal and temperature dispersion from nuclear power plants), exploration and management of coastal karst, changing perceptions of dune management, advances in interpretation of sea-level indicators and real time environmental monitoring. New advances in both environmental management and governance are of the utmost importance for sustaining critical coastal marine areas. Offering such a diverse collection of works from coastal scientists around the world, who discuss many techniques and methods at the forefront of management and governance, this publication will be of interest to coastal researchers, coastal zone managers and regulatory agency personnel.